PENGARUH FREKUENSI PEMBERIAN PAKAN YANG BERBEDA TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN BENIH IKAN SILAIS (Ompok hypophthalmus) - Mulyadi '; Usman MT; Suryani ' (Fakultas Perikanan dan Kelautan, Universitas Riau, 2010)
The research was conducted from March to May 2009, in the Laboratory ofAquaculture Technology of Fisheries and Marine Science Faculty, RiauUniversity. The aim of research was to investigate frequency of fish mealdistribution on growth and survival rate of Ompok hypophthalmus.In this research, 3 treatments with 4 replications was applied. Fish used inthis research were 4 to 4,5 cm in length. Stocking density of fish was 15fish/aquaria. Fish meal frequency applied was 3, 4 and 5 times/day. Fish diet usedin the research was commersial pellet with given doses of 10 % from fish bodyweight. Based on Anova analysis, results showed that the fish meal distribution of5 times/day gave the best result on growth of 13,42 g, fish diet efficiency 35,90 %and survival rate of 100 %.